An investigation into the difficulties that teachers and students face in using new English textbook 8 at lower secondary schools in Nghe An - Bùi, Thị Thu Hà (University of Languages and International Studies, 2017)
Part A: Introduction. Part B: Development (Chapter one: Literature review. Chapter two: An overview of English language teaching in Vietnam and introduction of the new english textbook 8. Chapter three: Methodology. Chapter four: Findings and discussion). Part 3: Conclusion